A new species of the genus Eucyclodes (Lepidoptera, Geometridae, Geometrinae) from China - Zhang, Xinyi; Wang, Wenkai; Han, Hongxiang (Zootaxa, 2019)
The genus Eucyclodes was originally established by Warren (1894) on the basis of Phorodesma buprestaria Guenée, 1858. Eucyclodes is a large genus, which contains more than 90 species (Scoble 1999; Scoble & Hausmann 2007), mainly distributed in the Indo-Australian tropics, and more than 50% of all species are found in New Guinea. More than 90% of all Eucyclodes species were described before the 1950s. The most recent additions were made by Inoue (1978, 1986), Holloway & Sommerer (1984), Holloway (1996), and Tautel (2016), who each erected one new species per publication. The tribal position of Eucyclodes is still uncertain, for example, Pitkin (1996), Holloway (1996) and Ban et al. (2018) placed it in the tribe Nemoriini (or Nemoriiti), and the most recent research by Murillo-Ramos et al. (2019) found that Eucyclodes is sister to other Nemoriini and the authors did not assign it to any tribe.